Quantifying the influence of varying centrifugation spin paces and timespans on serum electrolyte dynamics in an Indian clinical laboratory - Maharana, Sunil K.; Adak, Shiuli R.; K. Dolui, Rupesh (International Journal of Research in Medical Sciences, 2024)
Background: A reduction in turnaround time at any laboratory is critical for early assessment. Our aim of the study was to evaluate the effects of various spin paces and timespans on certain serum electrolyte concentrations, such as sodium (Na+), potassium (K+), and chloride (Cl-). Methods: A cross-sectional, observational study was carried out on 66 apparently healthy volunteers. 10 ml of blood was drawn from each and divided into 4 labelled clot vials (2.5 ml in each vial). Concentrations of serum Na+, K+, and Cl- were assessed in 2 groups (1, 2), each with 33 individuals. Group 1 had varying spin pace parameters (1500 rpm, 2500 rpm, 3500 rpm, and 4500 rpm), and group 2 included various timespans (2 min, 5 min, 10 min, and 15 min). The observations were analyzed using statistical package for the social sciences (SPSS). Analysis of variance (ANOVA) was implied along with a post-hoc Tukey test. A p value of <0.05 was considered statistically significant. Results: Mean concentrations of Na+, K+, and Cl- at different spin paces for a fixed runtime of 2mins had statistically no differences between each other: Na+ (p=0.978), K+ (p 0.999), and Cl- (p=0.997). However, there were statistically significant mean differences at various timespans for Na+ (p<0.001), K+ (p<0.001), and Cl- (p<0.001). Conclusions: Our study concludes that Na+, K+, and Cl- concentrations were not altered at various spin paces. A timespan of 2 mins at 4500 rpm outperformed the benchmarks without affecting the results, signifying that it can be routinely chosen for estimating serum electrolytes such as Na+, K+, and Cl-, effectively lowering turnaround time.